EVALUASI SEDIAAN SABUN MANDI CAIR EKSTRAK ETANOL DAUN JAMBU BOL (Syizigium malaccense L.) - Reubun, Yonathan Tri Atmodjo; Batubara, Kevin Septiyanto (Jurnal Farmasi & Sains Indonesia, 2023)
Bath soap is a skin care cosmetic product that can moisturize and protect the skin from sunlight and dirt that comes from outside. Of the various forms of soap preparations on the market, one type of soap that is currently being produced is in liquid dosage form because its use is more practical and the form is more attractive than other forms of soap. The use of natural ingredients as bath soap has been widely used in several soap products, one of the plants that can be used as an active ingredient in liquid soap is guava leaves. The purpose of this study was to determine the antioxidant activity of the ethanol extract of guava leaves (Syizigium malaccense L.) in liquid body soap preparations. The method used in this study was extraction using 96% ethanol solvent and the formulation of liquid bath soap was carried out, after which tests were carried out which included organoleptic tests, foam height tests, specific gravity tests, stability tests, and antioxidant activity tests. The results showed that the ethanol extract liquid bath soap of guava leaves is brown in color, liquid in shape, has a characteristic odor, and has a smooth texture. The foam height test result was 2 cm, the specific gravity test result was 1.020 g/mL and the antioxidant activity test result for the guava bol ethanol extract liquid bath soap was 9.6898. The conclusion of this study is that guava leaf extract can be used as a liquid bath soap preparation and has a good inhibitory concentration based on the results.